2021
DOI: 10.1017/asr.2020.122
|View full text |Cite
|
Sign up to set email alerts
|

African Responses to COVID-19: The Reckoning of Agency?

Abstract: Although the COVID-19 pandemic had claimed over one million lives globally by late 2020, Africa had avoided a massive outbreak. Patterson and Balogun analyze pandemic responses by the Africa Centres for Disease Control and Prevention and various states collaborating with civil society. They argue that responses display forms of agency rooted in contextually relevant expertise, pan-African solidarity, and lessons learned about health messaging and community mobilization from previous health crises. Yet collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…plan health responses. [11][12][13] National health research systems serve as a key component of a state's ability to respond to both acute and long-term health needs. 14 They, however, have also been seen to provide key economic development opportunities through specialised areas of expertise, high-tech employment, and innovation.…”
Section: Key Messagesmentioning
confidence: 99%
“…plan health responses. [11][12][13] National health research systems serve as a key component of a state's ability to respond to both acute and long-term health needs. 14 They, however, have also been seen to provide key economic development opportunities through specialised areas of expertise, high-tech employment, and innovation.…”
Section: Key Messagesmentioning
confidence: 99%
“…Research has demonstrated the importance of social media platforms such as Facebook for both political engagement and health information dissemination (Patterson & Balogun 2021). These various platforms afford different capabilities to users.…”
Section: Humor Health and Repression In Quotidian Politicsmentioning
confidence: 99%
“…Regional organisations are increasingly involved in health policy matters within their broader sectoral integration mandates, [1] including in Africa [2,3]. Public health emergencies such as the 2014 Ebola outbreak and current COVID-19 pandemic have highlighted the unique roles that regional organisations in Africa can play in coordination, resource pooling, or scientific leadership when they have institutional capacity for these [4][5][6]. The involvement of regional organisations in epidemics and disease control has been identified as a way to strengthen regional cooperation in health within Africa through diplomacy, with such organisations seen to be operating at the interface of global health institutions and national governments-seeking to represent and act on their shared interests, align strategies, promote a unified position, or mobilise partnerships [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging this history of regional bodies on the African continent and their health programmes and policies [2,3,[48][49][50], with emerging knowledge about their roles in health research [5,39,45], there is still much unknown about the constellation of actors in regionalism for health sciences research (HSciR). Therefore, this study aims to map the state-based regional organisations in Africa involved in HSciR, characterise the network of actors, and test the hypothesis of whether regional network strength correlates with national health research indicators.…”
Section: Introductionmentioning
confidence: 99%